805 External Validation of the McGovern Score for Predicting Pediatric Blunt Cerebrovascular Injury. (April 2023) - Venkataraman, Sidish Srinivas; Herbert, Joseph; Ravindra, Vijay; Bollo, Robert John; Cox, Charles S.; Gannon, Stephen; Limbrick, David Delmar; Naftel, Robert Partlow; Ugalde, Irma; Weiner, Howard; Yorkgitis, Brian; Shah, Manish N.
Abstract : INTRODUCTION: Blunt cerebrovascular injury (BCVI) is defined as blunt trauma to the head and neck leading to damage to the vertebral and/or carotid arteries. The risk factors for pediatric BCVI have not been clearly described and which pediatric patients are considered "high-risk" and in need of angiographic/vessel imaging is largely based on clinical and institutional treatment patterns. Our group previously proposed a screening tool, the McGovern score, to identify pediatric trauma patients at high risk for BCVI. METHODS: This multicenter, retrospective, hospital-based, cohort study involved data collected for all pediatric (<16 years) trauma patients who presented to the emergency department between 2003 and 2017 at 6 level 1 pediatric trauma centers. This trauma registry was then queried for patients who received a CTA as a screening method for BCVI. Patient age, arrival date, length of follow-up, and MOI were recorded. Glasgow Coma Scale (GCS) on arrival and the presence or absence of a focal neurological deficit. The obtained radiological variables included the presence or absence of a carotid canal fracture, petrous temporal bone fracture, and cerebral infarction as determined on CT scanning. Patients who were found to have BCVI were queried for mode of treatment, type of intracranial injury, artery damaged, and BCVI injury grade. The McGovern score was calculated for all patients who underwent CTA across all data groups. RESULTS: 1012 patients underwent CTA. 72 of these patients were found to have BCVI, 51 of which were in the external cohort. Across all data groups, the McGovern score has a >80% sensitivity and >98% NPV. CONCLUSIONS: The McGovern score is an effective and generalizable screening tool for pediatric BCVI.